Effect of Cooperative Learning Methods, Command and Motion Coordination on Basic Volleyball Techniques - Deri Putra; Resdianto, Resdianto; Indah, Deby (Universitas Majalengka, 2024)
The problem in this study is that there are still many extracurricular students at SMP Negeri 02 Rambah Samo who do not have good basic engineering skills. This can be seen when serving, passing, passing. When viewed at the time of service, the coordination of the movement has not yet continued subsequently. When doing bottom passes most students cannot master the ball properly. Likewise when passing on mistakes that are often made by students is the technique of mastering the fingers with the ball still stiff so that the ball is somewhat held up (double). In this study using a quasi experimental research method, with the aim of research to determine the effect of learning methods and motion coordination on mastering basic volleyball techniques of SMP Negeri 02 Rambah Samo students used descriptive research with quantitative analysis approach. While the skills of the upper pass and lower pass with a quantitative analysis approach using the Volleyball test Repeated (repetition). Service skills use a test service (After that will be followed by an experiment with a factorial 2x2 design. The population in this study were all male students who took part in the volleyball extracurricular activities at SMP Negeri 02 Rambah Samo, with 44 male students. The sampling technique in this study total sampling technique is used. The results of the research and analysis of this data show that: (1). There are differences in the results of the volleyball base technique possessed by extracurricular students of SMP 02 Rambah Samo who were trained using cooperative learning methods and command learning methods. (2). There is an interaction between cooperative learning methods, command and movement coordination possessed by volleyball players on basic techniques ... (3). Students who have high motion coordination will have basic volleyball techniques that are no better if trained with cooperative learning methods than the command learning method. (4). Players who have low motion coordination will have better techniques if trained with cooperative learning methods rather than command learning methods.